2008
DOI: 10.1371/journal.pone.0003332
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Misexpression Screen Uncovers a Role for Enabled in Progressive Neurodegeneration

Abstract: Drosophila is a well-established model to study the molecular basis of neurodegenerative diseases. We carried out a misexpression screen to identify genes involved in neurodegeneration examining locomotor behavior in young and aged flies. We hypothesized that a progressive loss of rhythmic activity could reveal novel genes involved in neurodegenerative mechanisms. One of the interesting candidates showing progressive arrhythmicity has reduced enabled (ena) levels. ena down-regulation gave rise to progressive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…Males were monitored for 3 d in LD 12:12 followed by 7 d in DD. We observed that the activity of aging flies was fragmented and extended into the night in LD (Figure 1A), similar to previous reports (Koh et al, 2006; Rezaval et al, 2008). Analysis of fly activity in DD revealed decreased proportion of rhythmic flies in 35- and 50-day-old flies (Figure 1B).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Males were monitored for 3 d in LD 12:12 followed by 7 d in DD. We observed that the activity of aging flies was fragmented and extended into the night in LD (Figure 1A), similar to previous reports (Koh et al, 2006; Rezaval et al, 2008). Analysis of fly activity in DD revealed decreased proportion of rhythmic flies in 35- and 50-day-old flies (Figure 1B).…”
Section: Resultssupporting
confidence: 92%
“…We addressed this question using Drosophila , which are short-lived and have a well-understood circadian system. First, we confirmed previous reports of deterioration of the circadian locomotor activity rhythm in aging flies (Koh et al, 2006; Rezaval et al, 2008). In our study, flies that remained rhythmic in DD showed significant lengthening of the free-running period of locomotor activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The links between AD and circadian rhythms were inferred from transgenic model animals expressing pathogenic versions of human genes (Rezaval et al, 2008; Roh et al, 2012; Sterniczuk et al, 2010). Recent reports showed that pathogenic human amyloid peptides disrupt behavioral rest-activity rhythms in Drosophila but are not sufficient to disrupt molecular oscillations of PERIOD (PER) in central pacemaker neurons (Chen et al, 2014; Long et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary antibodies (1:250; Jackson ImmunoResearch) were Cy2-conjugated donkey anti-rat, Cy5-conjugated donkey anti-mouse and Cy3-conjugated donkey anti-rabbit. Incubation was for 3 h at 23 C, and the brains were then rinsed 5 times in PT for 25 min each followed by a long rinse overnight a 4 C. Brains were mounted in 80% glycerol in PT (Rezával et al, 2008).…”
Section: Dissections and Immunofluorescencementioning
confidence: 99%